Limitations in Serbia's copper export: exploring solutions for enhanced export performance - Stanojevic, Natasa (Industrija, 2025)
The analysis of the deteriorated export structure of the copper industry unveils two primary challenges: a shortage of skilled labour and insufficient processing capacity, exacerbated by increased exploitation under new ownership. These issues cannot be fully resolved before final depletion of copper mines. Therefore, this research focuses on identifying solutions to improve copper export structure in given limiting conditions. Quantitative research using the RCA index and share in total export identifies three copper product groups with the greatest potential for export enhancement: refined copper (HS7403), plates, sheets, and strips (HS7409), and copper tubes and pipes (HS7411). Redirecting limited processing capacities and human resources towards the improvement of only these products would provide a more favourable balance between raw ore and processed copper. This approach would likely result in higher profits and the potential to utilize the capacities of associated activities, as these products undergo a significantly higher degree of processing compared to ore.
Keywords: copper industry, copper exports, Serbia, RCA index